Regulatory policy and corporate homogeneity: a configurational comparative analysis of the occupational health and safety reform in 2010 - Refslund, Bjarke (Politica, 2016)
Public policy often assumes that companies are a homogenous group, especially companies of a certain size. This assumption might be problematic, and the analysis tests the assumption on 14 companies and their implementation of the occupational health and safety (OHS) reform in Denmark in 2010 as well as the configuration of conditions leading to the outcome. The configurational analysis shows significant variation in the companies’ implementation of the legislative changes despite elements of reflexive legislation in the reform. The reflexivity in the regulation should enhance the companies’ ability to implement the changes. The analysis shows, among other things, that a lack of professional OHS organisation and employee involvement in the companies is a major obstacle to implementation of the reform.